2002
DOI: 10.1128/aem.68.10.4835-4840.2002
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Hemoglobins and Flavohemoglobins for Alleviation of Nitrosative Stress in Escherichia coli

Abstract: Escherichia coli MG1655 cells expressing novel bacterial hemoglobin and flavohemoglobin genes from a medium-copy-number plasmid were grown in shake flask cultures under nitrosative and oxidative stress. E. coli cells expressing these proteins display enhanced resistance against the NO ⅐ releaser sodium nitroprusside (SNP) relative to that of the control strain bearing the parental plasmid. Expression of bacterial hemoglobins originating from Campylobacter jejuni (CHb) and Vitreoscilla sp. (VHb) conferred resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
82
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 41 publications
1
82
0
1
Order By: Relevance
“…Single domain globins are produced by a small number of bacterial species such as Vitreoscilla sp., Campylobacter jejuni, and Mycobacterium bovis (51,52). But the role of these globins is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Single domain globins are produced by a small number of bacterial species such as Vitreoscilla sp., Campylobacter jejuni, and Mycobacterium bovis (51,52). But the role of these globins is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Additionally, Gram-negative bacteria such as E. coli, K. pneumoniae and P. aeruginosa synthesize flavohemoglobins (Hmp), enzymes that neutralize NO and therefore counteract nitrosative stress. 28 Under aerobic conditions, Hmp are upregulated in the presence of NO acting as a denitrosylase that downgrade NO to a harmless NO 3 -ion. Therefore it was not surprising that Bioscreen and CFU analysis demonstrated that the Gram-positive organisms were more susceptible to NO-np, requiring lower concentrations to achieve a significant inhibitory effect on growth and survival as compared to the Gram-negative organisms evaluated.…”
mentioning
confidence: 99%
“…1B) and modulates the geometry of proximal site is substituted by an alanine. The data suggest that the proximal histidine of MtbFHb lacks the peroxidase-like imidazolate character present in a typical FHb (7,20). The reductase domain of MtbFHb is also highly modified.…”
Section: Unusual Structural Features Of Heme and Reductasementioning
confidence: 74%
“…The most notable difference is the lack of hydrogen-bonding interactions between F8H-H23E-G5Y (Fig. 1, A and B) at the proximal site that is conserved among FHb family (7,8). Additionally, H12Y that interacts directly with G5Y (Fig.…”
Section: Unusual Structural Features Of Heme and Reductasementioning
confidence: 99%
See 1 more Smart Citation